>10% Efficiency Polymer:Fullerene Solar Cells with Polyacetylene‐Based Polyelectrolyte Interlayers. Issue 23 (2nd November 2016) - Nam, Sungho; Seo, Jooyeok; Han, Hyemi; Kim, Hwajeong; Hahm, Suk Gyu; Ree, Moonhor; Gal, Yeong‐Soon; Anthopoulos, Thomas D.; Bradley, Donal D. C.; Kim, Youngkyoo
Abstract : Polymer solar cells have gained great attention due to their tremendous potential for applications in light‐weight, large‐area, and flexible photovoltaic modules fabricated via continuous roll‐to‐roll processes. Despite the significant progress, however, their efficiency and operating stability are still inadequate for commercial applications. Interfacial engineering of the electron‐collecting buffer layer and the organic photoactive layer through the use of organic dipole interlayers, has been proposed as a simple and scalable way to improve the overall solar cell performance. Here, highly efficient inverted polymer:fullerene solar cells have been successfully developed with a power conversion efficiency of over 10%. The bulk heterojunction layer consists of the poly[4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b]dithiophene‐alt‐3‐fluorothieno[3, 4‐b]thiophene‐2‐carboxylate] (PTB7‐Th) and the [6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PC71 BM), as the electron donor and electron acceptor, respectively. Key to this success is the insertion of the ionic polyacetylene‐based conjugated polymer, poly(N‐dodecyl‐2‐ethynylpyridinium bromide), as an interfacial dipole layer. The latter is shown to lower the work function of the electron transporting zinc oxide layer and increase the built‐in potential, consequently facilitating efficient charge transport/extraction. Optimized solar cells exhibit power conversion efficiency values exceeding 10% while their operating stability under continuous solar‐simulated illumination is significantly enhanced when ultraviolet light is effectively blocked using a suitable optical filter. Abstract : The polyacetylene‐based polyelectrolyte interlayers significantly enhance the efficiency and stability of polymer:fullerene solar cells due to their conformal coatings on the metal oxide electron‐collecting buffer layers.